Respuesta :
Answer:
HERE YOU GO
Step-by-step explanation:
x2 - 4x + 2 + y2 - 4y + 2 = 4 : expand equation of first circle
x2 - 2x + 1 + y2 - 2y + 1 = 4 : expand equation of second circle
-2x - 2y - 6 = 0 : subtract the left and right terms of the above equations
y = 3 - x : solve the above for y.
2x2 - 6x + 1 = 0 : substitute y by 3 - x in the first equation, expand and group like terms.
(3/2 + √(7)/2 , 3/2 - √(7)/2) , (3/2 - √(7)/2 , 3/2 + √(7)/2) : solve the above for x and use y = 3 - x to find y.